Wat bezielt afvalligen? Een narratieve analyse van post-christelijke identiteitsontwikkelingen naar atheïsme of holistische spiritualiteit - van 't Hul, Leonard (Religie & Samenleving, 2022)
Social scientists have come up with contrasting ideas on how to interpret individual transitions toward post-Christian identities in contemporary Western societies. From the 1990s onward there has been a growing scientific interest in transitions towards holistic spiritualities, a trend that was complemented by an increasing emphasis on secular identities such as atheism after the turn of the millennium. A review of this growing stock of academic literature shows that the theoretical explanations of the various diagnoses are remarkably the same, emphasizing a rationalization and pluralization of (religious) meaning systems, and a growth of moral individualism. Although these notions are undeniably true, they hardly enable a differentiation between individual transitions to the complementing post-Christian identities. In this article I delve into this ‘explanatory gap’ by comparatively reconstructing the trajectories of post-Christian identity reshaping, while focusing on the transition to atheist disbelief and holistic spiritualities. From a series of life course interviews it appears that the strictness of one’s religious milieu is a paramount factor in the process toward apostasy and embracing a new religious or secular identity later in life.